HISTORICAL REVIEW OF AGRICULTURAL COOPERATION: WORLD TRENDS AND UKRAINIAN REALITIES - Viktor BORSHCHEVSKYY; Halyna KAPLENKO; Inna KULISH; Nataliya PAK; Oksana PIKULYK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article is aimed at studying the state of agricultural cooperation in Ukraine in a historical retrospective. It is shown that before the October Revolution of 1917, cooperation in the country successfully developed, was profitable and convenient for participants in cooperatives. The methods of pseudo-cooperation, which were practiced in the USSR and received the collective name "collectivization", are analyzed. It has been proved that collectivization and cooperation differ in essence; this is confirmed by the unprofitability of collective farms and the fact that they consistently received subsidies from the state. The main problems of agricultural cooperation in Ukraine from 1991 to the present time are revealed. The regulatory and legal support of this sphere and its change are analyzed, taking into account the international documents signed by Ukraine, as well as Ukraine's obtaining the status of a candidate country for joining the European Union. It is shown that at the present stage, under martial law, the functioning and development of cooperation is difficult, but there is reason to expect an improvement in the situation after the cessation of hostilities on the territory of Ukraine. The statistics used in this study are taken from the official website of the State Department of Statistics of Ukraine; records of agricultural cooperatives have been kept since 2004.